Welander's distal myopathy: clinical, neurophysiological and muscle biopsy observations in young and middle aged adults with early symptoms. Issue 6 (June 1991) - Borg, K; Ahlberg, G; Borg, J; Edström, L
Abstract : Nine young or middle aged patients with early symptoms of Welander's distal myopathy were subjected to a detailed neurological examination including quantitative sensory testing, determination of motor and sensory nerve conduction velocity (NCV), sensory nerve action potentials, electromyography (EMG) and muscle biopsy from the tibialis anterior muscle (TA). Slight weakness of the extensors of the fingers and hands was found in all nine patients, and of the dorsiflexors of the feet in seven. All patients had a distal sensory disturbance most prominent for temperature which agrees with earlier observations. EMG changes in TA and extensor digitorum communis (EDC) muscles were of myopathic type. Slight abnormalities compatible with either myopathy or early neuropathy were found in one muscle biopsy. These findings indicate that a neurogenic lesion affecting at least the peripheral sensory system is present at an early stage of Welander's distal myopathy and that the neurogenic lesion might precede the myopathic changes.